An initial e-Learning 3.0 framework for higher-education universities in Malaysia - Sofiadin, A.; Issa, Tomayess (IADIS Press, 2012)
Technology becomes an essential instrument and practice in the higher - education sector, and among individuals and organizations to advance specific skills in communication, collaboration, sharing knowledge, and gaining cutting edge. There are various types of technologies to support it, ranged from Web 1.0; Web 2.0 and current Web 3.0. Web 3.0 is called the Semantic Web; that manages information in a dramatic logical way as it allows the Artificial Intelligence (AI) methods applied to big data; which lead to a new learning model called e-learning 3.0. E-learning 3.0 will assist students to obtain a better understanding of the learning process. To improve the relationship between higher-education stakeholders (i.e. Students, academics and administrator's authorities), the researcher examined and assessed various types of models and framework in e-learning and specifically in e-learning 3.0, to develop an initial new e-learning 3.0 framework for higher education in Malaysia. This paper, will present the new initial framework, who will support the self-directed and continuous learning and the potential to hare e-learning knowledge by providing better access to key resources to support e-learning and improve user interaction and student satisfaction.